Oral glucose lowering drugs in type 2 diabetic patients with chronic kidney disease - Nogueira, C (2013)
Chronic kidney disease (CKD) represents a challenge in the treatment of type 2 diabetic patients. Renal impairment may affect drug clearance and other pharmacokinetic processes which can increase toxicity and drug to drug interactions or cause ineffective therapy. There are many oral glucose lowering drugs available for the treatment of type 2 diabetes mellitus (T2DM) with different mechanisms of action and different pharmacokinetic profiles. While all classes may be used in patients with mild renal impairment, therapeutic options for patients with moderate to severe CKD are still limited. This review focuses on the pharmacokinetics, metabolism, and safety of oral glucose lowering drugs in patients with T2DM and CKD.